THE EFFECT OF USING EGRA (EXPOSURE, GENERALIZATION, REINFORCEMENT, APPLICATION) METHOD IN TEACHING PASSIVE VOICE AT THE ELEVENTH GRADE STUDENTS OF SMA NEGERI 2 SIABU 2018/2019 ACADEMIC YEAR - Yusuf Apandi Harahap (JURNAL LINER (Language Intelligence and Educational Research), 2020)
Abstract: The objective of this research is to know whether there is a significant effect of EGRA method in teaching passive voice at the eleventh grade students of SMA Negeri 2 Siabu. This research uses experimental method with the experimental research design; one group pre-test and post-test design. The population is all of the eleventh grade students which consist of 92 students. Technique sampling that used on this research is systematic sampling and the number of the sample consists of 30 students. In collecting the data, the researcher uses observation sheet to get the data of the application of EGRA method and test to get the data is multiple choices. The researcher uses statistic process in analyzing by using t test formula. Based on the data that has been analyzed, the result of analyzed data showed that t test is higher than t table (t test 4.79 > t table 2.04), and the hypothesis is accepted. It means that there is a significant effect of using EGRA (exposure, generalization, reinforcement, application) method in teaching passive voice at the eleventh grade students of SMA Negeri 2 Siabu. Keywords: EGRA method, passive voice. Abstrak: Tujuan penelitian ini adalah untuk mengetahui apakah ada sebuah pengaruh yang signifikan dari EGRA method dalam mengajarkan passive voice di kelas sebelas SMA Negeri 2 Siabu. Penelitian ini menggunakan metode eksperimental dengan rancangan penelitian experimental; one group pre-test post-test design. Populasi penelitian terdiri dari 92 siswa kelas sebelas. Teknik penarikan sampel yang digunakan dalam penelitian ini adalah penarikan sampel sistematis dan jumlah sample terdiri dari 30 siswa. Dalam pengumpulan data, peneliti menggunakan lembar observasi untuk menjaring data dari pengaplikasian EGRA method dan tes untuk menjaring data mengenai passive voice adalah pilihan ganda. Peneliti menggunakan proses statistik dalam analisis data, yaitu rumus tes t. Berdasarkan data yang telah di analisis, hasil analisis data menunjukkan bahwa t hitung lebih besar dari pada t table (t hitung 4.79 > t table 2.04), dan, hipotesis diterima. Hal ini berarti ada sebuah pengaruh yang signifikan dari EGRA method terhadap pengajaran passive voice di kelas sebelas SMA Negeri 2 Siabu. Kata kunci: metode EGRA, passive voice.